Perception scores of siblings and parents of children with hypoplastic left heart syndrome. (17th July 2018) - Caris, Elizabeth C.; Dempster, Nicole; Wernovsky, Gil; Miao, Yongjie; Moore‐Clingenpeel, Melissa; Neely, Trent; Fonseca, Rachel; Miller‐Tate, Holly; Allen, Robin; Fichtner, Samantha; Stewart, Jamie; Cua, Clifford L.
Abstract: Objectives: Siblings of children with chronic medical conditions endorse a lower quality of life compared to age‐matched peers. Caregiver and sibling‐self report of adjustment are often discordant. Congenital heart disease significantly affects family life. To date, there have been no studies addressing the functioning of siblings of children with hypoplastic left heart syndrome, one of the most severe forms of congenital heart disease. The goal of this study was to assess the impact of hypoplastic left heart syndrome on sibling's quality of life as well as the caregiver's perception of this effect. Study Design: Cross‐sectional study using a web‐based survey distributed via various listservs targeted towards families of children with hypoplastic left heart syndrome. Employed the Sibling Perception Questionnaire, designed to assess sibling and caregiver perceptions of adjustment to chronic illness. A Negative Adjustment Composite Score was calculated for each respondent, with higher values representing more negative adjustment. Results: Thirty‐five caregivers responded. Majority of caregivers were female (74%), white (86%) and college educated (54%). Thirty‐two siblings participated, ranging in age from 7 to 30 years of age (12.5 ± 6.3). Most children with hypoplastic left heart syndrome (73%) had undergone the third stage of palliation. Forty‐two caregiver‐sibling pairs were examined. Caregiver Negative Adjustment Composite Scores were significantly higher than sibling scores, with caregivers reporting more adjustment problems (2.4 ± 0.4) than siblings (2.3 ± 0.3, P  < .05). Sibling age was correlated with worse caregiver and sibling scores (r 0.35, P  < .05). Conclusions: Caregivers of children with hypoplastic left heart syndrome perceive their siblings as struggling more than the children self‐report. Siblings tend to report worse adjustment as they get older. These data suggest that programs should include support for the entire family through all ages to optimize quality of life.